2021
DOI: 10.3390/ijms221910821
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Models for Agonists and Antagonists of Molecular Initiation Events for Toxicity Pathways Using an Improved Deep-Learning-Based Quantitative Structure–Activity Relationship System

Abstract: In silico approaches have been studied intensively to assess the toxicological risk of various chemical compounds as alternatives to traditional in vivo animal tests. Among these approaches, quantitative structure–activity relationship (QSAR) analysis has the advantages that it is able to construct models to predict the biological properties of chemicals based on structural information. Previously, we reported a deep learning (DL) algorithm-based QSAR approach called DeepSnap-DL for high-performance prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…In addition, the highest prediction performance values of F on the valid dataset for the angles and datasplit ratios were 0.935 at 176 • and train:valid:test = 7:1:2 in 720725_GR_ant, 0.914 at 176 • and train:valid:test = 3:1:2 in 1347030_TRHR_ago, and 0.876 at 176 • and train:valid:test = 7:1:2 in 1347032_TGF_beta_ant (Figures S11 and S12; Table 3). In this study, we observed two performance peaks in prediction models at 176 • and 355 • of angles in DeepSnap, according to previous results [53,54]. These findings suggested that image augmentation is effectively worked.…”
Section: Angles and Data Split In Deepsnap-dl With Digits And Python ...supporting
confidence: 88%
See 4 more Smart Citations
“…In addition, the highest prediction performance values of F on the valid dataset for the angles and datasplit ratios were 0.935 at 176 • and train:valid:test = 7:1:2 in 720725_GR_ant, 0.914 at 176 • and train:valid:test = 3:1:2 in 1347030_TRHR_ago, and 0.876 at 176 • and train:valid:test = 7:1:2 in 1347032_TGF_beta_ant (Figures S11 and S12; Table 3). In this study, we observed two performance peaks in prediction models at 176 • and 355 • of angles in DeepSnap, according to previous results [53,54]. These findings suggested that image augmentation is effectively worked.…”
Section: Angles and Data Split In Deepsnap-dl With Digits And Python ...supporting
confidence: 88%
“…The prediction models using the DeepSnap-DL system achieved higher performance than conventional ML techniques, such as random forest, XGBoost, LightGBM, and CatBoost [51,52]. Additionally, prediction models of MIE molecule agonist or antagonist activity were constructed using by the DeepSnap-DL system with the Tox21 10k library, suggesting this system as essential tool for novel QSAR analysis due to automatic feature extraction with numerous structural information from a 3D-chemical structure [53,54]. For high-throughput of the DeepSnap-DL system, automation in the DeepSanp-DL system has been conducted by combining each process consisting of the generation of images from a 3D-chemical structure based on the simplified molecular input line entry system (SMILES) format, DL using these images as input data, and calculation of prediction-performance indexes using TensorFlow and Keras [54].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations